ANALYSIS OF THE APPLICATION OF INTRAOSTEAL IMPLANTS IMPLIFE SOLO ® OF SMALL DIAMETER - Korol, D.M. (World of Medicine and Biology, 2012)
The author analyses five-year experience of the application of dental intraosteal implants Implife Solo with the diameter of 3,0 mm produced by “Inpride Ltd” (Ukraine) in versatile anatomic and topographic areas of both maxilla and mandible.
Keywords: itraosteal implantation; immediate loading; one-stage implant